MENINGKATKAN KEAKTIFAN BELAJAR PENDIDIKAN AGAMA KATOLIK MELALUI METODE KOOPERATIF TIPE KANCING GEMERINCING BAGI SISWA KELAS X SOSIAL 1 SMAN 1 MALAKA TIMUR TAHUN AJARAN 2022/2021 - Bau, Nikolas; Usboko, Wilibrordus Cornelis; Mones, Anselmus Yata (Selidik (Jurnal Seputar Penelitian Pendidikan Keagamaan), 2022)
This research was conducted to determine the quality of the process of implementing the rattling button type cooperative method which can increase learning activity in Class This research includes classroom action research (PTK) which consists of cycle I and cycle II, each of which has four stages, namely: planning stage, implementation stage, observation stage and reflection stage. The techniques used in data collection are observation, tests and research documentation. The results of the research show that the application of the rattling button type cooperative method can increase learning activity in Catholic religious education, where in cycle I student activity was 75.53% with fairly good criteria, and in cycle II student activity increased 95.92% with very good criteria. Based on the research results obtained, the researchers concluded that through the cooperative method of the jingling button type can increase the learning activity of Class X Social 1 students at SMAN 1 East Malaka for the 2022/2023 academic year.